2010
DOI: 10.1590/s0034-737x2010000300015
|View full text |Cite
|
Sign up to set email alerts
|

Sistemas de produção de feijão intercalado com cafeeiro adensado em período de formação ou após recepa

Abstract: Production systems of bean intercropped with establishing coffee crop or after stumpingIntercropping of annual crops with coffee crop has been used since the introduction of coffee cultivation in Brazil. However, the last available results have been obtained with old cultivars and exceeded distance between lines. Aiming to study the effect of row numbers and NPK doses applied to bean intercropped with coffee trees, two field experiments were conducted at the Federal University of Lavras. The experiments were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
(7 reference statements)
1
1
0
1
Order By: Relevance
“…Around 95% of farmers produced beans in Rwanda (Blair et al, 2010). These results were similar to those of Carvalho et al (2010) who showed that the beans associated with coffee significantly increased in production regardless of the fertilizer dose and crop management. In Rwanda, beans were an essential source of proteins for all farmers who are unable to get proteins from animal products.…”
Section: Allsupporting
confidence: 86%
“…Around 95% of farmers produced beans in Rwanda (Blair et al, 2010). These results were similar to those of Carvalho et al (2010) who showed that the beans associated with coffee significantly increased in production regardless of the fertilizer dose and crop management. In Rwanda, beans were an essential source of proteins for all farmers who are unable to get proteins from animal products.…”
Section: Allsupporting
confidence: 86%
“…The same authors checked a variation from 24.2 g (control) to 29.7 g (75 kg ha -1 N + 25 kg ha -1 P 2 O 5 ). Carvalho et al (2010),studying beans intercropped with coffee, established that NPK use with irrigation enhanced linearly 100GW values of common beans; however, the NPK dose increase in non-irrigated plants promoted decrease of this variable.…”
Section: Resultsmentioning
confidence: 99%
“…Várias espécies de plantas com características distintas como porte, hábito de crescimento e produção de biomassa podem ser utilizadas como cobertura de solo em sistemas de consórcio com cafeeiros (Matos et al, 2008). Espécies como o milho e feijoeiro são boas opções para esse manejo, pois além de ser um dos alimentos básicos da alimentação brasileira, são plantas de ciclo curto, pouco competitivas e com relativa tolerância à competição imposta pela planta consorte (Carvalho et al, 2010). Esse consórcio é preferido principalmente pelos agricultores familiares que aperfeiçoam o uso da área com maior diversificação de produtos, custeando a implantação da lavoura cafeeira .…”
unclassified